Antenna systems for IoT applications: a review - Sunawar Khan; Tehseen Mazhar; Tariq Shahzad; Afsha Bibi; Wasim Ahmad; Muhammad Amir Khan; Mamoon M. Saeed; Habib Hamam (Discover Sustainability)
Abstract In smart homes, industrial automation, healthcare, agriculture, and environmental monitoring, IoT antenna systems improve communication efficiency and dependability. IoT antenna systems affect network performance and connection by affecting gain, directivity, bandwidth, efficiency, and impedance matching. Dipole, patch, spiral, metamaterial-based, and other antenna types are tested in IoT settings to identify their applicability, benefits, and downsides. Current antenna technology has challenges with frequency, bandwidth, size, weight, material choices, and energy efficiency, requiring new solutions. According to the study, interference control, power consumption, and dynamic IoT adaptation research are inadequate. Metamaterials, nanomaterials, and 3D printing may circumvent these antenna design limitations. AI and machine learning can improve antenna design real-time optimization and performance in complex settings. The paper explores how standards and regulatory frameworks affect IoT antenna system development to ensure future designs meet a fast-growing market. For the growing range of IoT applications, this research suggests more flexible and reconfigurable antennas that can function across numerous frequency bands. The report emphasizes antenna material and design innovation to improve durability, cut costs, and scale manufacturing. This research tackles these key elements to enable the next generation of antenna systems to meet IoT technology's expanding needs and increase networked devices' functionality, efficiency, and integration across industries. This comprehensive approach helps identify current trends and concerns and prepares for future IoT antenna system advancements, enabling smarter, more connected, and more efficient technologies.